Potential of anaerobic rumen fungi Orpinomyces joyonii to degrade lignified feedstuffs - Kumar, S; Seghal, J P; Mir, Ishtiyak A; Jha, P; Ganie, Azaz A (The Indian Journal of Animal Sciences, 2012)
The work was carried out to study the enzymes p- coumaroyl esterase, p-feruloyl esterase activity and in vitro fiber digestibility of wheat straw, paddy straw and total mixed ration (paddy straw: wheat straws: concentrate mixture in the ratio of 30:30:40) incorporated with the zoospores of anaerobic rumen fungi Orpinomyces joyonii. Significant increase in p-coumaroyl and p-feruloyl esterase activity was observed when Orpinomyces joyonii were incubated with paddy straw, wheat straw and TMR based medium as compared to control (without Orpinomyces joyonii). In vitro fiber digestibility of paddy straw, wheat straw and TMR increased significantly as compared to their respective control. It might be concluded that there were 5.0–9.7, 2.3–5.0 and 2.4–3.7% increase in IVDM, IVNDF and IVADF digestibility of paddy straw, wheat straw and total mixed ration incorporated with the zoospores of anaerobic rumen fungi Orpinomyces joyonii.